O pacto nacional pela alfabetização na idade certa: implicações teórico-metodológicas na formação do professor alfabetizador - Xavier, Elizete Divina (2017)
The Ministry of Education and Culture (MEC) program titled National Pact for Literacy in the Proper Age (PNAIC), which aims to alphabetize all children, without exception and at the right time: by the end of third grade. Like others states and counties, Goiás State Secretary Department of Education had joined the program. This work is based on it, especially in order to discuss what is proposed as theoretical and methodological concepts in literacy to teach reading and writing and its implications in literacy teachers. The initial hypothesis suggested that in Language's Notebooks, this study object, the subject's concepts, communication and language, for example, were saw in a psychologizing perspective, without giving emphasis to language's issues and without considering children's and teacher's subjectivity related to knowledge, hypothesis confirmed throughout this research. This study has a qualitative and documental bibliographic nature and was based on Linguistics and Psychoanalysis studies references, discussing languages concepts, language and subject. Chapter 1 approaches PNAIC beginning on national leveland and its development on Goiás State relating the documents that establish it legally and its organizational structure. Chapter 2 presents PNAIC notebook's language, and what they bring as communication, lenguage and subject's conceptions. Chapter 3 presents a discussion about the need where teachers must produce reading and writing experiences in literacy by having an elaboration perspective and therefore presents a proposal of a training course which aims to contribute to the continuing education of literacy teachers in Goiás State.